Preface Volume 27 (2) Year 2026 - Rahman, Andri (BRIN Publishing (Penerbit BRIN), 2026)
Materials science and technology development plays an active role in several fields of life including medicine, infrastructure, energy, computational material science, and others. Researchers and academics are at the forefront of this development. Indonesia Journal of Materials Science ( JUSAMI) was founded to represent their needs, which are now widely recognized as an integral part of scientific and characterization investigations. JUSAMI Vol. 27 No. 2, Year 2026 is proudly published several paper entitled: 1) The Influence of pH on Structural, Morphological, and Optical Properties of Al2O3 Nanoparticles Synthesized by Syzygium aromaticum Leaf Extract; 2) High Temperature Corrosion On Inconel and Carbon Steel Filler of Weldment in Liquid Pb at 800 ̊C; 3) Glucose Detection Using a Surface Plasmon Resonance Biosensor Functionalized by Glucose Oxidase; 4) Enhanced Co₂ Adsorption Using Activated Carbon From Tea Stem Waste Via Activation–Carbonization Strategy; 5) Synthesis and Characterization of Biocompatible Facial Sheet Masks Utilizing Ginger Cellulose and Jicama Starch; 6) Characteristics and Photocatalytic Performance of Coprecipitation Praseodymium (Pr)-doped Strontium Titanate for Methylene Blue Degradation; 7) Density and Tensile Properties Analysis of Biocomposite from Lid Film Waste and Oil Palm Empty Fruit Bunch Fiber; 8) Physical and Mechanical Properties of Chitosan Bioplastics with Ramie Fiber Concentration Variations.